Late Paleogene sinistral strike-slip system along east Qinling and in southern North China: Implications for interaction between collision-related block trans-rotation and subduction-related back-arc extension in East China - Zhang, Yueqiao; Dong, Shuwen; Li, Jianhua (Tectonophysics, 2019)
We present in this paper a compilation of Paleogene rift and strike-slip structures in east Qinling and southern North China based on a synthesis of published stratigraphic, structural and thermochronological data, which aids in delineating a broad (>500-km-wide), kinematically interlinked, Eocene-Oligocene transtensional system. This transtensional system was bifurcated from two discrete strike-slip fault zones in NE Tibetan Plateau. The overall fault patterns indicate a clockwise rotation of South China relative to North China during the Cenozoic, possibly driven by dextral shearing along the eastern Tibetan margin. This collision-related trans-rotation of South China occurred coevally with late Paleogene intracontinental rifting and volcanism in East China in a subduction-related back-arc extensional setting. These two tectonic processes interacted with each other, giving birth to Cenozoic rift systems and contrasting morpho-structural features in East Asia. •Delineation of Paleogene rifts in East China and major rifting phases and tectonic inversion events.•Depicting late Paleogene sinistral strike-slip system along east Qinling.•Interaction between collision-related transrotation and subduction-related back-arc extension in East China.